THERAPEUTIC POTENTIAL OF LACTOBACILLI-BASED DRUG IN THE TREATMENT OF GENERALIZED PERIODONTITIS - Petrushanko, T.O.; Loban, G.A.; Moshel, T.N.; Hancho, O.V. (World of Medicine and Biology, 2020)
The article presented the study results on the method of generalized periodontitis treatment with lactobacilli-based probiotic drug. Its efficacy was accessed according to generally accepted clinical and microbiological studies in the treatment dynamics in patients with stages I and II of generalized, chronic periodontitis on the 1st, 5th and 10th day of follow-up. Treatment of periodontitis included professional oral hygiene, topical and common application of probiotics. Probiotic application for the treatment of generalized periodontitis contributed to the improvement of oral health (p
Keywords: generalized periodontitis; probiotic; lactobacilli; microflora of gingival pockets